Антропологічний склад населення черняхівської культури Північного Причорномор’я - Рудич, Т.О. (Археологія, 2003)
Велика територія поширення черняхівської культури потребує розгляду антропологічного складу населення за регіональним принципом. Це дає змогу чіткіше й детальніше виявити особливості черняхівського населення цієї території і риси, які є спільними для усієї культури. В статье дан анализ краниологических материалов, происходящих из погребений с трупоположениями могильников Черняховской культуры Северного Причерноморья.
В суммарном выражении серия Черняховской культуры этого региона характеризуется, с одной стороны, близостью к населению позднескифских памятников Северного Причерноморья и античных центров, а с другой — к антропологическому материалу из могильников Черняховской культуры лесостепной зоны. Присутствуют в серии также морфотипы, которые не имеют истоков на данной территории, а ближайшие аналогии известны в Центральной и Северной Европе. Их появление может быть связано с готскими миграциями.
Местные и пришлые элементы на могильниках Черняховской культуры Северного Причерноморья представлены в разных пропорциях на разных могильниках, что определяет характер их морфологических связей. Черняховское население Нижнего Днепра (Гавриловка) статистически близко к вестготским сериям VI—VII вв., а также сериям из Прибалтики I—V вв. н. э. Население Южнобугско-Тилигульского междуречья близко к Черняховским группам Среднего Поднепровья и Левобережной Украины, поздним скифам, а также населению античных городов. Это хорошо иллюстрирует смешанность группы. Население Буджака статистически и морфологически близко как к лесостепным черняховским сериям, так и к позднескифским. Женская серия Черняховских могильников Буджака близка к сборной серии Черняховской культуры Западной Украины и сериям вельбарской культуры Польши. Морфотип женской серии характерен для населения западных и северных районов Украины, а также восточных районов Польши в эпоху средневековья. The article analyzes craniological materials of the sepultures-inhumation of burial grounds of Chemiakhivs’ka culture on territory to the north of the northern coast of the Black Sea. On the whole a stuff of Chemiakhivs’ka culture of this region reveals a similarity with population of late Scythian sites on the northern coast of the Black Sea North and ancient towns of Greeks on the one hand and with anthropological materials of the burial grounds of Chemiakhivs’ka culture in the forest-steppe zone on the other hand. There are also morphotypes in stuff which are no provenance on this territory and close by analogy in the central and northern Europe. Their arising can link on migration of Goth. Native and foreign elements on burial grounds of Chemiakhivs’ka culture are in different proportions on different burial grounds that determines the nature of their morphological links. The population which left Chemiakhivs’ka culture in the Low Dnieper (Gavrylivka) closesis Visigothic series of the 6th-7th centuries statistically and also series of the southeastern coast of the Baltic Sea dating AD from the 1st to the 5th centuries. Population of the River Southern Bug and the River Southern Bug and the River Telegul interfluve closes groups of Chemiakhivs’ka culture on the Middle Dnieper and on the territories to the left from the River Dnieper, late Scythians as well as population of ancient towns of Greeks. It shows mixing inside of group. Population of Budgak closes statistically and morphologically both series of Chemiakhivs’ka culture in the forest-steppe zone and late Scythian. A series of female of burial ground of Chemiakhivs’ka culture in Budgak closes a combined series of Chemiakhivs’ka culture in the western Ukraine and series of Velbars’ka cultures in Poland. The morphotype of female series will be typical for population of the western and northern regions of Ukraine as well as of eastern regions of Poland in the Middle Ages.